The role of investigative reports on news pages on social networks and its relationship to shaping the public’s attitudes toward government performance - Maytham Falih Hussein (Genius Journals, 2023)
The aim of this study is to evaluate investigative issues on newspaper pages across social networks on public issues. The researcher used the purposive sampling method to obtain progress. A sample was taken from the city of Baghdad, divided into two areas (Al-Rusafa and Al-Karkh) by distributing a questionnaire as data methods. The researcher summarized the study and suggested building on the results of the analysis and suggested successful solutions to it. It concluded investigated, but the government's use of independent media for self-censorship and lack of access to unregulated organizations and experts present challenges. It is expected that social media networks will have their role, and have become a public media, on public issues, but thanks to the research results, social media pages have become its new role. Therefore, it has to diversify its programming issues and strive to implement its oversight role.
Keywords: Investigative reporting; news pages; Social networks